Comparison of Percutaneous Cystolithotomy and Vesicolithotomy in Large Vesical Stones - Dastgir, Munzir Bin; Samore, Muhammad Akmal; Javaid, Waleed; Haji, Muhammad; Irshad, Rana Farrukh; Hussain, Qamrosh (Indus Journal of Bioscience Research, 2025)
Objectives: comparison of percutaneous cystolithotomy and vesicolithotomy in large vesical stones. Study Settings: This randomized controlled trial was conducted at the Department of Urology, DHQ Hospital Faisalabad. Duration of Study: The study was conducted over a period of six months following ethical approval. Data Collection: A total of 60 patients, aged 18–60 years, with large vesical stones (2–4 cm in diameter) were randomly assigned to two groups: Group A (OV) and Group B (PCCL). For PCCL, the urinary bladder was filled using an 8Fr feeding tube, and a suprapubic puncture was performed with an 18-gauge spinal needle. A guide wire was inserted, followed by serial dilatation and the placement of a 28Fr amplatz sheath. A nephroscope was used to locate and remove the stone with a triple-jaw stone grasper. Population data, operative time, and hospital stay were recorded. Results: The mean operative time was significantly shorter in the B group (38.20 ± 9.94 minutes) compared to the A group (71.16 ± 13.13 minutes, p = 0.000). Similarly, hospital stay was significantly reduced in the B group (1.47 ± 0.56 days) compared to the A group (2.51 ± 0.67 days, p = 0.000). Conclusion: PCCL is an effective and minimally invasive alternative to OV for managing large vesical stones, offering less hospital duration and operative time. These findings support the integration of PCCL into routine clinical practice.